The effects of learning experience on college students’ deep english learning: a study of the chain mediation effect of motivation and strategy - Qun Zhang; Hao Jin; Wen Wen Teng (PLoS ONE, 2025)
This study focuses on the impact of learning experience on college students’ deep learning of English and the chain-mediated effects of motivation and strategy. In the context of globalization, English is crucial for university students, but traditional teaching models often neglect the role of learning experience in deep learning. Deep learning emphasizes critical understanding, creative application and long-term memory construction, which is particularly important for English learning. Learning experience covers affective, cognitive and behavioral responses, and influences learning attitudes and effects, but there are fewer studies on its impact on college students’ deep learning of English and the related mechanisms. In this study, college students of different genders, ages, educational backgrounds and academic achievement levels were selected as samples, and learning experience, motivation, learning strategies and deep learning were comprehensively assessed by well-designed scales and statistically analyzed with the help of SPSS and AMOS software. The results of the study show that learning experience has a significant positive effect on English deep learning, and motivation and learning strategies play an important chain mediating role. Specifically, learning experience enhances motivation, which in turn promotes the use of learning strategies and ultimately improves English deep learning. This study validates for the first time the chain mediation model of “learning experience→learning motivation→learning strategies→deep learning”in the field of English language learning, which provides a new perspective for understanding the intrinsic mechanism of college students’ English language learning and enriches related research. In practice, it provides specific guidance for English teaching, and teachers can enhance students’ English deep learning by optimizing learning experience, stimulating learning motivation and guiding the use of learning strategies. However, there are some limitations in this study, such as the limited sample scope and the use of a cross-sectional design, etc. Future studies can expand the sample scope, adopt a longitudinal research design, and further explore other potential mediating variables.